Comparison of indications of pregnancy termination and prognosis of mothers and neonates in early- and late-onset preeclampsia. (2nd July 2016) - Ni, Yanyan; Cheng, Weiwei
ABSTRACT: Objective : To compare the indications of pregnancy termination and prognosis between early-onset preeclampsia (EOP) and late-onset preeclampsia (LOP). Methods : In total, 100 patients diagnosed early-onset preeclampsia in our hospital from January 1, 2012, to June 30, 2014, were recruited for this retrospective cohort study. At the same time, we randomly chose another 100 late-onset preeclampsia as the contrast group. Criterion distinguishing early versus late was set at week 34 of gestation. Indications for pregnancy termination and prognosis of mothers and neonates were compared between the groups. Results : Significant differences were observed between the groups regarding indications for terminating pregnancy. The EOP indications to terminate the pregnancy were mainly fetal-related, while LOP were mainly maternal-related. Postpartum neonatal morbidity and mortality were significantly higher, mean gestational age onset and delivery were significantly earlier, latent period for delivery and postpartum hospitalization time were significantly longer, admission 24 h proteinuria was significantly higher in EOP than in LOP group ( P < 0.05). Conclusion : EOP is a distinct and more severe clinical entity with earlier gestational age onset and delivery. EOP might be a fetal-related disease complicated by severe placental and perinatal injuries; LOP might be a maternal-related derived disease condition.